2020
DOI: 10.1097/j.pain.0000000000002170
|View full text |Cite
|
Sign up to set email alerts
|

Fear-avoidance beliefs are associated with reduced lumbar spine flexion during object lifting in pain-free adults

Abstract: Pain-related fear is associated with less lumbar flexion during lifting in pain-free adults, indicating a protective movement strategy in the absence of low back pain.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 72 publications
5
31
0
Order By: Relevance
“…= 0.0496; p = 0.242). This finding for TSK-total is consistent with some studies [22,28] but not with others [18,31], which is most likely due to a variety of different methodological approaches as well as different population characteristics. In addition, a conditioning process due to task-specific pain experiences might elicit an altered behavioral or muscular reaction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…= 0.0496; p = 0.242). This finding for TSK-total is consistent with some studies [22,28] but not with others [18,31], which is most likely due to a variety of different methodological approaches as well as different population characteristics. In addition, a conditioning process due to task-specific pain experiences might elicit an altered behavioral or muscular reaction.…”
Section: Discussionsupporting
confidence: 91%
“…To avoid lumbar flexion and remain an upright position of the back, muscular activation of trunk muscles, especially of the erector spinae is required [21,24,27]. This goes along with the results from Knechtle et al [22], which showed a reduced flexion of the lumbar spine (particularly in the L4/L5 region) in healthy individuals with high task-specific fear during object lifting. This again supports the assumption of movement adaption through a change of muscular activity in the lower lumbar back driven by fear avoidance beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, this lifting technique is advocated in manual handling training to reduce the risk of LBP [9]. Although this cross-sectional study cannot determine the cause-effect relationship of LBP related to lifting, or the reason for the differences seen in lifting technique, previous research has demonstrated that people both with LBP [42,43] and without LBP [44], who have higher levels of pain-related fear, lift with less lumbar flexion. There is also evidence that as people with chronic LBP improve, how they perform activities such as bending and lifting becomes faster with greater lumbar ROM in most cases [45].…”
Section: Aim 1 -Comparison Of Lifting Technique Between Lbp and Nolbp Groupsmentioning
confidence: 90%